Inverted U-shaped relationships between managerial ownership and impression management: evidence from China before and during COVID-19 pandemic - Kwok Yip Cheung; Chung Yee Lai (Cogent Business & Management)
Impression management refers to controlling or shaping the information disclosed to affect readers’ interpretations. Managers may manipulate the tone and length of financial reports to manage stakeholders’ expectations. This exploratory study examines the impact of managerial ownership on impression management using Management Discussion and Analysis (MD&A) reports contained in annual reports for all A-shares listed in China from 2018 to 2021. In total, 5279 firm-year observations were collected from China. The results suggest that managerial ownership has a significantly inverted U-shaped relationship with impression management, indicating that executives who hold ownership in a company are more likely to engage in impression management. However, beyond 31% of managerial ownership, the effectiveness of oversight quality on impression management is strengthened, leading to decreased levels of impression management. This relationship is more prevalent during the COVID-19 pandemic (2020 and 2021). The findings of this study provide policy implications not only for China but also for Asian countries with similar institutional backgrounds. For example, managerial ownership should not be restricted to below 31%. Additionally, the findings provide additional mechanisms for investors to identify impression management during unstable financial periods.